Examining the effects of pre-competition rapid weight loss on hydration status and competition performance in elite judo athletes - Bialowas, D.; Laskowski, R.; Franchini, E.; Kujach, S. (Scientific Reports, 2023)
The prevalence of rapid weight loss (RWL) among martial arts athletes including judo is very high. Many applied RWL strategies could be dangerous to health and even lead to death. Therefore, the International Judo Federation (IJF) introduced changes in the weigh-in rules, changing the official weigh-in for the day before the competition. Thus, the purpose of this study was to examine the impact of the new IJF rules on hydration status and weight loss strategies among professional judo athletes. Seventeen elite judo athletes participated in the study. Body mass and hydration status, were analyzed before the competition. Moreover, competition result and practice of RWL survey were collected. All subjects reached their weight category limits for the competition. RWL resulted in body mass changes (p < 0.001, Etap2 = 0.79) and dehydration among participants (urine osmolality > 700 [mOsmol*kg]-1 and urine specific gravity > 1.020 [g*cm3]-1). However, urine osmolality (p > 0.05, Etap2 = 0.18), as well as urine specific gravity (p > 0.05, Etap2 = 0.16), at subsequent time points of measurement revealed no statistical differences. The prevalence of RWL was 100%, and only 17.6% of the athletes declared that they would compete in a different weight category if the competition would be conducted on the same day of the weigh-in. All judo athletes applied RWL procedures using traditional methods to achieve the required body mass (i.e., increased exercise, reduced fluid, and food intake). Dehydration state was not associated with competitive performance (p > 0.05).